2002
DOI: 10.1039/b202200a
|View full text |Cite
|
Sign up to set email alerts
|

A novel piezo-optical styrene sensor incorporating polymer-supported tribromide ion

Abstract: Encapsulation of Amberlyst A-26 supported tribromide in a 10,000 MW polyethylene glycol matrix gives a robust colour-sensitive reagent matrix which can be deposited on indium-tin oxide coated polyvinylidene fluoride (PVDF) piezoelectric film for the detection of styrene (and other alkene) vapours.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…As a potential human carcinogen, styrene vapor may be harmful to skin, eyes, and respiratory system. At high levels (10,000 ppm) of styrene vapor, rats and pigs become comatose after several minutes, even died after 30 to 60 min of exposure 58 . Therefore, it is necessary to develop convenient and reliable sensors for the styrene detection.…”
Section: Voc Decoding In Vapormentioning
confidence: 99%
“…As a potential human carcinogen, styrene vapor may be harmful to skin, eyes, and respiratory system. At high levels (10,000 ppm) of styrene vapor, rats and pigs become comatose after several minutes, even died after 30 to 60 min of exposure 58 . Therefore, it is necessary to develop convenient and reliable sensors for the styrene detection.…”
Section: Voc Decoding In Vapormentioning
confidence: 99%
“…Its main applications are related to the production of polystyrene and copolymers (e.g. ABS and SBR rubber) [2], and synthetic composite resins like fiberglass [3][4][5]. Fiberglass is widely used in the ship industry, since its mechanical and chemical properties make it suitable for long term application in highly reactive environments, such as seawater [6].…”
Section: Introductionmentioning
confidence: 99%
“…Dosimeters for styrene exposure have been reported in literature. Back in 2002, Bearman et al [2] proposed a piezo-optical styrene sensor to be used for dosimetry that employed a modified polyvinylidene fluoride (PVDF) layer capable of changing its piezoelectric behaviour upon interaction with styrene under a light source. Recently, Radica et al [25] reported a hybrid organic/inorganic device based on a tetraethylortho-silicate and phenyltriethoxysilane polymer film used to monitor styrene through infrared spectroscopy.…”
Section: Introductionmentioning
confidence: 99%
“…This is based on the PiezOptic system, which we have described in detail previously. [11][12][13][14][15][16] The system consists of a badge (Fig. 1 and 2) that may be used for many different analytes with appropriate reagents, and a reader unit (Fig.…”
Section: Introductionmentioning
confidence: 99%